2015
DOI: 10.1038/bjc.2015.81
|View full text |Cite|
|
Sign up to set email alerts
|

A distinct pre-existing inflammatory tumour microenvironment is associated with chemotherapy resistance in high-grade serous epithelial ovarian cancer

Abstract: Background:Chemotherapy resistance is a major determinant of poor overall survival rates in high-grade serous ovarian cancer (HGSC). We have previously shown that gene expression alterations affecting the NF-κB pathway characterise chemotherapy resistance in HGSC, suggesting that the regulation of an immune response may be associated with this phenotype.Methods:Given that intrinsic drug resistance pre-exists and is governed by both tumour and host factors, the current study was performed to examine the cross-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 42 publications
(50 reference statements)
6
65
0
6
Order By: Relevance
“…7 The preexisting inflammatory tumor microenvironment has recently been shown to be associated with the innate response to chemotherapy in several types of cancer, including ovarian HGSC. 8 The existence of the extracellular matrix closely associated with the tumor may influence the drug response phenotype, and this strengthens the idea that the tumor microenvironment may have an immunomodulatory effect on tumor behavior. 9,10 Therefore, biomarkers that inform on the immune microenvironment are good candidates for evaluation when searching for new ways of predicting the therapeutic response.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…7 The preexisting inflammatory tumor microenvironment has recently been shown to be associated with the innate response to chemotherapy in several types of cancer, including ovarian HGSC. 8 The existence of the extracellular matrix closely associated with the tumor may influence the drug response phenotype, and this strengthens the idea that the tumor microenvironment may have an immunomodulatory effect on tumor behavior. 9,10 Therefore, biomarkers that inform on the immune microenvironment are good candidates for evaluation when searching for new ways of predicting the therapeutic response.…”
mentioning
confidence: 57%
“…8 This study showed that a distinct STAT1-dependent tumor inflammatory microenvironment was associated with chemotherapy response in ovarian HGSC.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…In this regard, it was recently reported that, in combination with doxorubicin, lurbinectedin has compelling activity as a second-line treatment in patients with SCLC (43), a tumor type that could be most sensitive to transcription-targeting drugs (3-5, 7, 44, 45). Lurbinectedin has also showed impressive activity in platinum-resistant ovarian cancer (46), a subtype of ovarian cancer that has been related to gene expression alterations affecting different oncogenic pathways related to drug resistance and tumor microenvironment (47)(48)(49). Targeting transcription addiction with lurbinectedin might be similarly beneficial in the treatment of other tumor types that are known to be dependent on transcription dysregulation (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 At this symposium, they present data that in chemosensitive tumors, there is upregulation of STAT1 and a type-I interferon pathway gene signature. Tumor cells with this gene signature may more effectively recruit CD8+ T-cells, resulting in a greater immunologic response and improved cancer cell treatment.…”
Section: Immune Cells In the Ovarian Cancer Tumor Microenvironmentmentioning
confidence: 99%